Papua New Guinea : Selected Issues Paper and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2010)
This Article IV Consultation reports that the main challenge is to maintain macroeconomic stability in substantial demand shock from the construction of two major liquefied natural gas projects. The global downturn had only a mild impact, as growth was supported by still strong terms of trade, a financial sector insulated from global capital markets, and an increase in public expenditure. IMF staff stressed that monetary policy needed to be focused on emerging inflation pressures and act preemptively to avoid high inflation from becoming entrenched in expectations.